Measuring language development in pervasive developmental disorders (PDD) and non-PDD children - Molly D. Oktarina; Hardiono D. Pusponegoro; Zakiudin Munasir (Indonesian Pediatric Society Publishing House, 2009)
Background Impairments in language and related social communication skills can be found in children with pervasive developmental disorders (POD) and other developmental language disorders (non-POD). These conditions lead to decision of enrolling children with language disorders to speech therapy despite that it is not the therapy of choice for POD. Objectives To explore the differences in receptive language, verbal expressive language, and non-verbal expressive language between PDD and non-POD children Methods A cross sectional study was performed in October 2008 to January 2009. Questionnaire using the MacArthur communicative development inventory (CDI) was filled by parents whose children were PDD and non-PDD patients aged 1 to 3 years old. The diagnosis ofPDD was based on the diagnostic and statistical manual IV. Results A total of 42 PDD and 42 non-POD subjects were evaluated. There was significant difference between PDD and non POD in receptive language [P= 0.01 (95% CI -170.63 to -24.33) in 12 to 24 month-old subjects and P< 0.01 (95% CI -158.28 to -92.99) in > 24 to 36 month-old subjects] and non-verbal expressive language [P= 0.01 (95% CI -20.96 to -1.96) in 12 to 24 month-old subjects and P< 0.01 (95% CI -22.65 to -10.5) in > 24 to 36 month-old subjects]. Verbal expressive language was not significantly different between POD and non-POD children age 1 to 3 year-old. Conclusions PDD children are more likely to have a delay in receptive language and non-verbal expressive language compare to non-POD children. Verbal expressive language can not be used to differentiate POD and non-POD children.